Opportunities in housing property for young and first-time homebuyer in Malaysia - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2022)
The biggest concern for first-time buyers is affordability, especially in major Malaysian cities such as Klang Valley, Penang and Johor. Low and middle-income families are worried because affordability will not only affect their ability to become homeowners, but also the size and type of houses they can buy. In order to solve the problem of affordability of real estate, the Malaysian government has provided two key programs for the relatively new workforce. However, most young and first-time buyers are not aware of these offers. This article aims to review the opportunities for young and first-time homebuyers to own a home. This article first reviews young and time homebuyers, the definition of housing, housing loans, the support provided by the Malaysian government for first-time homebuyers in terms of affordable housing and financial support.